Neutralizing antibodies for the prevention and treatment of COVID-19 - Du, Lanying; Yang, Yang; Zhang, Xiujuan (Cellular & molecular immunology, 2021)
Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) initiates the infection process by binding to the viral cellular receptor angiotensin-converting enzyme 2 through the receptor-binding domain (RBD) in the S1 subunit of the viral spike (S) protein. This event is followed by virus-cell membrane fusion mediated by the S2 subunit, which allows virus entry into the host cell. Therefore, the SARS-CoV-2 S protein is a key therapeutic target, and prevention and treatment of coronavirus disease 2019 (COVID-19) have focused on the development of neutralizing monoclonal antibodies (nAbs) that target this protein. In this review, we summarize the nAbs targeting SARS-CoV-2 proteins that have been developed to date, with a focus on the N-terminal domain and RBD of the S protein. We also describe the roles that binding affinity, neutralizing activity, and protection provided by these nAbs play in the prevention and treatment of COVID-19 and discuss the potential to improve nAb efficiency against multiple SARS-CoV-2 variants. This review provides important information for the development of effective nAbs with broad-spectrum activity against current and future SARS-CoV-2 strains.